SYNTHESIS, CHARACTERIZATION AND BIOLOGICAL PROPERTIES OF NEW CODEINE FE(III) COMPLEX - Ghamami, Shahriar; Golzani, Mojdeh; Lashgari, Amir (Journal of the Chilean Chemical Society, 2016)
The reaction of FeCl3hexahydrate with C18H20NO3.PO4 in acetonitrile produced new complex with general formula [Fe(L)]Cl2, (L= codeine). Characterization of the ligand and its complex were made by elemental analysis, FT-IR, 1H-NMR, Raman and UV–visible spectroscopy. This new complex showed antitumor activity against two kinds of cancer cell lines: AGS (Stomach) and MCF-7 (Breast). Cell cytotoxic effects of the ligand and its complex were assayed by MTT and Natural-red tests. The antibacterial activity of ligand and complex against Pseudomonas aeruginosa, Staphylococcus aureus, Streptococcus pyogenes and Escherichia coli were also examined.